The magic faraway tree, Moonface's story - Beech, Mark (Hodder children's book, London, 2022)
In this delightful tale, Moonface, a beloved character from the Magic Faraway Tree series, wishes to host a birthday party for his friends. However, his attempt to bake a cake results in a burnt disaster. Determined to salvage the celebration, Moonface seeks assistance from the magical lands atop the Faraway Tree. This enchanting story introduces young readers to the whimsical world of the Faraway Tree, featuring familiar characters like Silky and the Saucepan Man. With vibrant illustrations by Mark Beech, the book is designed for shared reading experiences with children aged 3 and over.